STUDI KASUS PENGEMBANGAN KOMODITI KENTANG DAN SERAI WANGI UNTUK PENGEMBANGAN KAWASAN AGROINDUSTRI - Jamilah Munir; Sunadi Sunadi; Milda Ernita; Syahrial Syahrial (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2022)
The development of the Agroindustrial Area is directed to Dua Koto District, Pasaman Regency. Dua Koto Subdistrict has superior commodities to be developed for food crops, horticulture, plantations, and industrial plants. Potato plants are horticultural crops and are able to live well in highland locations (>800 m asl), as well as coffee plantations, areca nut, and citronella can grow well from the middle to the highlands. Oil palm and rubber plantations turned out to be unprofitable. The purpose of the activity was to analyze soil and environmental conditions on the potential for the development of biodiversity for several superior products to reach the agro-industrial area. This research activity was carried out using survey methods and interviews with the community and village officials. From the results of the discussion, it was concluded that Oxisol and Ultisol soil types in the Cubadak village, Dua Koto sub-district, which are in the highlands (> 800 m asl) is suitable for potato development with the addition of sufficient organic matter and artificial fertilizers. Oil palm and rubber plants will be not recommended to be planted or included in the agroforestry pattern in the highlands, because they are not suitable for agro-climatic conditions. It is necessary to develop coffee plants in an agroforestry pattern as well as intercropping with potato plants. Planting distance of 50 x 50 cm citronella plants, with a selling price of Rp. 165,000/kg of fresh material, Feasibility reaches 18.68, with an average profit of Rp. 7,808,333,-/month/ha. There needs to be an efficient spacing of citronella plants with cutting slope planting techniques, so that the production per hectare can exceed the average product in Indonesia, to reach an agro-industrial area.